2021
DOI: 10.3389/fpsyg.2021.778970
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Evaluation of the Impact of Using Rapport-Based Interviewing Approaches With Child Sexual Abuse Suspects

Abstract: Two studies examined whether rapport-based interviewing with child sexual abuse (CSA) suspects provides greater interview yield that could result in overall cost-savings to the investigation. First, multi-level modelling was applied to 35 naturalistic CSA suspect interviews to establish whether rapport-based interviewing techniques increase “yield” – defined as information of investigative value. The Observing Rapport Based Interviewing Technique (ORBIT coding manual was used to code interviews; it includes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Crucially, this article also sits in tandem with research evaluating the economic benefits of adaptive and MI interviewing. Giles et al (2021) found in their review that the estimated cost savings are between £157 million and £639 million for all CSA, increasing to between £2 billion and £8 billion when accounting for averted lifetime costs on victims. Thus, the benefits of treating CSA suspects fairly and with respect are twofold: increased information-gathering success and cost savings for law enforcement nationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, this article also sits in tandem with research evaluating the economic benefits of adaptive and MI interviewing. Giles et al (2021) found in their review that the estimated cost savings are between £157 million and £639 million for all CSA, increasing to between £2 billion and £8 billion when accounting for averted lifetime costs on victims. Thus, the benefits of treating CSA suspects fairly and with respect are twofold: increased information-gathering success and cost savings for law enforcement nationally.…”
Section: Discussionmentioning
confidence: 99%
“…It found research support for the use of a rapport-based, empathic, and interpersonally competent approach to interviewing CSA suspects. Further, recently Giles et al (2021) conducted an economic evaluation of rapport-based approaches with CSA offenders. They found that training in adaptive and MI approaches could contribute to cost savings between £19 million and £78 million (annual unit costs) increasing to between £238 million and £639 million (lifetime costs) for online CSA across England and Wales; and between £157 million and £639 million (annual unit costs) increasing to between £2 billion and £8 billion (lifetime costs) for all CSA interviewing.…”
Section: Suspect Interviewingmentioning
confidence: 99%